Default mode network connectivity and treatment response in geriatric depression. Issue 4 (1st March 2022) - Kilpatrick, Lisa A.; Krause‐Sorio, Beatrix; Siddarth, Prabha; Narr, Katherine L.; Lavretsky, Helen
Abstract: Objectives: Default mode network (DMN) connectivity is altered in depression. We evaluated the relationship between changes in within‐network DMN connectivity and improvement in depression in a subsample of our parent clinical trial comparing escitalopram/memantine (ESC/MEM) to escitalopram/placebo (ESC/PBO) in older depressed adults (NCT01902004). Methods: Twenty‐six participants with major depression (age > 60 years) and subjective memory complaints underwent treatment with ESC/MEM ( n  = 13) or ESC/PBO ( n  = 13), and completed baseline and 3‐month follow‐up resting state magnetic resonance imaging scans. Multi‐block partial least squares correlation analysis was used to evaluate the impact of treatment on within‐network DMN connectivity changes and their relationship with symptom improvement at 3 months (controlling for age and sex). Results: A significant latent variable was identified, reflecting within‐network DMN connectivity changes correlated with symptom improvement ( p  = .01). Specifically, although overall group differences in within‐network DMN connectivity changes failed to reach significance, increased within‐network connectivity of posterior/lateral DMN regions (precuneus, angular gyrus, superior/middle temporal cortex) was more strongly and positively correlated with symptom improvement in the ESC/MEM group ( r  = 0.97, 95% confidence interval: 0.86–0.98) than in the ESC/PBO group ( r  = 0.36, 95% confidence interval: 0.13–0.72). Conclusions: Increased within‐network connectivity of core DMN nodes was more strongly correlated with depressive symptom improvement with ESC/MEM than with ESC/PBO, supporting an improved engagement of brain circuitry implicated in the amelioration of depressive symptoms with combined ESC/MEM treatment in older adults with depression and subjective memory complaints. Abstract : We evaluated the relationship between changes in DMN connectivity and improvement in depression in a subsample of our parent clinical trial comparing escitalopram/memantine (ESC/MEM) to escitalopram/placebo (ESC/PBO) in older depressed adults (NCT01902004). A significant latent variable was identified, reflecting DMN connectivity changes related to symptom improvement. Increased connectivity of core DMN nodes was more strongly associated with depressive symptom improvement with ESC/MEM than with ESC/PBO, supporting a neuroplastic effect of memantine addition to escitalopram on brain circuitry that can help reduce depressive symptoms and prevent cognitive decline.